2004
DOI: 10.1007/s10038-004-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of multiple endocrine neoplasia type 1 in a young woman with a novel mutation of the MEN1 gene

Abstract: We report an unusual presentation of multiple endocrine neoplasia type 1 (MEN 1) in a young woman who was subsequently proven to have a novel mutation of the MEN1 gene. The young patient, aged 25 years, was investigated for abdominal discomfort and left upper abdominal pain. Her family history was unremarkable, except an unknown disorder of her father causing early death. Abdominal ultrasonography (USG) and computed tomography revealed a giant pancreatic tumor measuring 10 cm in diameter. The diagnosis of a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Four of these mutations have not been described previously. Two nonsense mutations (C354X and Q209X), two insertions (nt317ins5bp and nt1657insC) and two deletions (nt738del4 and nt359del4) have already been reported in our previous studies 24,26 . A screen for gene copy number alterations has not been performed in most studies on MEN1 including ours.…”
Section: Discussionmentioning
confidence: 82%
“…Four of these mutations have not been described previously. Two nonsense mutations (C354X and Q209X), two insertions (nt317ins5bp and nt1657insC) and two deletions (nt738del4 and nt359del4) have already been reported in our previous studies 24,26 . A screen for gene copy number alterations has not been performed in most studies on MEN1 including ours.…”
Section: Discussionmentioning
confidence: 82%
“…The c.202_206dupGCCCC mutation in exon 2 was identified in two probands. Ten mutations were described in our previous studies [13, 16], and further eight mutations have been reported formerly in the literature. To the best of our knowledge, of the 24 MEN1 gene mutations, five (c.19 C>T, p.Gln7STOP in exon 2; c.1160delA in exon 8; c.1399delG in exon 10; c.166_167insA in exon 2 and c.168delC in exon 2) have not yet been published, thus these were regarded as novel mutations (chromatograms of the mutated sequences can be found in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%